The Implementation of Understanding by Design Approach in Mathematics Learning on Elementary School - Nadhira Pramesti; Laksmi Dewi (IKIP Siliwangi, 2023)
This research is motivated by the lack of understanding of students in learning. Understanding by Design (UbD) can be implemented in the planning and implementation of learning to overcome these problems. Such as learning that is only focused on the teacher, the lack of involvement of students in the learning process so that students are less able to build their own understanding concepts. The purpose of this study is to determine the implementation of Understanding by Design in planning and implementing mathematic learning. In this reseach using the Systematic Literature Review method by collecting around 50 journal articles relevant to the research which were then re-selected. Understanding by Design (UbD) emphasizes understanding of students, in the process UbD uses a backwards design where the first thing to do is to determine what results are expected, then determine acceptable evidence, then in the last stage arrange steps in learning activities according to needs and learning objectives. Based on literature studies that have been carried out using a number of articles that are relevant to research and have gone through a re-selection process, the implementation of Understanding by Design (UbD) in learning is proven to increase students' mathematic understanding because in this learning students are actively involved so that learning is not teacher centered and this design can be an alternative learning design to improve the quality of education.